Kardiochirurgia dorosłychEpicardial versus endocardial radiofrequency ablation – two methods of atrial fibrillation treatment, two groups of patients - Sielicki, Piotr; Mokrzycki, Krzysztof; Żych, Andrzej; Todorowska, Agnieszka; Biskupski, Andrzej; Brykczyński, Mirosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Atrial fibrillation is the most frequent form of rhythm disturbances found in clinical practice. It increases the risk of stroke and risk of death. Often it is recognized among patients needing cardiac surgery. Aim: To compare early results of surgical treatment of atrial fibrillation using epicardial and endocardial radiofrequency ablation. Material and Methods: A retrospective study of 115 consecutive patients operated on from January 2006 to March 2008 was performed. 47 mitral valve prostheses, 22 mitral rings and 29 aortic valve prostheses were implanted. CABG/OPCAB alone or as a concomitant procedure was performed in 53 patients. Atrial fibrillation both paroxysmal or permanent was diagnosed in every case. Radiofrequency ablation of the left atrium using the MEDTRONIC CARDIOBLATE system was performed as a concomitant procedure – in 74 patients endocardial ablation using a monopolar device and in 41 patients epicardial ablation using a bipolar device. All patients had echocardiography and ECG performed pre- and postoperatively. Results: Mean ejection fraction was good, 52.5% (range 25–75%), and remained unchanged after the procedure, 50.2%. Mean EuroSCORE logistic was high, 5.18% (range 0.9–23.4): 3.9% in patients treated with epicardial ablation and 5.38% in patients treated with endocardial ablation. Mean length of stay was 9.7 days (range 4–42). Mean LA diameter assessed preoperatively was 51.2 mm: 39.7 mm in patients treated with epicardial ablation and 55.9 mm in patients treated with endocardial ablation. On the day of discharge from hospital 77.4% of patients were in sinus rhythm: 82.9% in patients after epicardial ablation and 74.3% in patients after endocardial ablation. Epicardial ablation was performed more frequently in patients with paroxysmal atrial fibrillation (44.9%) than permanent (27.6%). All patients with atrial flutter diagnosed preoperatively were discharged from hospital in sinus rhythm. In the group with permanent atrial fibrillation return of sinus rhythm was noted in 69% and 81.6% in the group with paroxysmal atrial fibrillation. 30-day mortality was 5.2% (6 deaths). Conclusions: Radiofrequency ablation is a safe method of supraventricular rhythm disturbance treatment and does not increase operative risk calculated according to the EuroSCORE logistic. Both epicardial and endocardial ablation are effective treatments of supraventricular rhythm disturbances. Results of endocardial ablation are worse, but patients treated with this method were at higher risk, more frequently with permanent atrial fibrillation and with wider left atrium.